The blue right : a public communication campaign to raise awareness of the right to clean water. - Ng, Cheryl Hui Hui. (2011)
This paper presents “The Blue Right” public communication campaign, a collaboration between four final year students from Nanyang Technological University Wee Kim Wee School of Communication, Lien Aid and Nanyang Environment and Water Research Institute (NEWRI). The campaign set out to raise awareness of water issues in Asia’s developing communities among undergraduates from the three public universities in Singapore: NTU, NUS and SMU. This paper includes conclusive research that shaped our key campaign strategies, communication plans and tactics, and presents an extensive evaluation of our campaign’s performance.